Data for conditional logistic regression for caribou - Courbin, Nicolas; Fortin, Daniel; Dussault, Christian; Courtois, R. (Dryad Digital Repository, 2014)
Data used to model the relative probability of used an inter-patch movement for caribou in winter as a function of network connectivity and landscape features (Tables 2 and 3). Covariates are provided at observed inter-patch movement and at available inter-patch movement.